Power, protest, and participation: local elites and the politics of development in India - Mitra, Subrata Kumar (Routledge, 1992)
Chapter 1 LOCAL ELITES AND THE POLITICS OF RURAL DEVELOPMENT -- chapter 2 THE REGIONAL CONTEXT: THE SOCIAL AND ECONOMIC BACKGROUND OF RURAL DEVELOPMENT -- chapter 3 THE ELEMENTS OF DESIGN -- chapter 4 SETTING THE LOCAL AGENDA: THE PROBLEMS, PROGRESS AND AGENCY OF RURAL DEVELOPMENT -- chapter 5 THE SOCIAL CONSTRUCTION OF LOCAL CONFLICT: UNEQUAL BENEFITS, RADICAL PROTEST AND SOCIAL COHESION -- chapter 6 INSTITUTIONAL PARTICIPATION AND RADICAL PROTEST: THE STATE, SOCIETY AND ROOM FOR MANOEUVRE IN THE MIDDLE -- chapter 7 CONCLUSION: THE TWO FACES OF DEVELOPMENT: PROTEST AND PARTICIPATION IN INDIA.
Includes bibliographical references (pages 290-306) and index. - Print version record
Keywords: India -- Politics and government -- 1947- -- India; India -- Politics and government -- 1947-; India; Electronic books; Agrarsoziologie; Elite; Indien; Ländliche Entwicklung